EFFECTS OF SELECTED MEDICINAL PLANTS ON RUMEN FERMENTATION IN A HIGH-CONCENTRATE DIET IN VITRO - M. Wencelová; Z. Váradyová; K. Mihaliková; D. Jalč; S. Kišidayová (Journal of Animal and Plant Sciences, 2014)
The objective of this in vitro study was to compare fermentation patterns of seven selected traditional medicinal plants and investigate the effects of medicinal plant mixture (MPM) supplements and a high-concentrate diet (lucerne hay and barley grain, LH+BG, 40:60) on rumen fermentation and fatty acid composition. An MPM of Taraxacum officinale L., Acorus calamus L., Calendula officinalis L., Hypericum perforatum L., Achillea millefolium L., Urtica dioica L. and Cichorium intybus L. was used. Qualitative phytochemical screening revealed the presence of medically active compounds (tannins, phenols, steroids, flavonoids, saponins, terpenoids and glycosides). The counts of total protozoan did not differ across medicinal plant fermentations and were positively correlated with the total SCFA concentration (P=0.002), methane production (P=0.001) and n-butyrate (P=0.011). Substitution of LH by MPM in proportions of 10%, 50% and 100% resulted in increased in vitro dry matter digestibility (by 6%) and decreased methane production (by 1%) in comparison with a diet without MPM. Only 100% supplementation with MPM increased the content of monounsaturated and polyunsaturated fatty acids, whereas the content of saturated fatty acids decreased in comparison with the diet without MPM. The results point to the promising beneficial effects of MPM in a high concentrate diet, with minimal adverse effect on rumen fermentation.
Keywords: Digestibility; batch culture; fermentation; ciliate protozoa; fatty acids; plants